Local Economic Development: A Conceptual Re-Articulation - Plaatjie, Sebeka Richard (Journal of Economics and Behavioral Studies, 2014)
Local economic development (LED) in the context of the development question is generally celebrated as a silver bullet to development challenges in Africa. However this discourse is more complex and needs greater theoretical scrutiny in order to understand its meaning. This paper picks up standpoint theory to critique the dominant understanding/s of local economic development and argues that unless it is more people-centered and benefits the local human/s, local economic development will remain an imposition from the top which will continue to alienate the local human and will remain an imperial project.